PERAMALAN REALISASI PENERIMAAN ZAKAT PADA BAITULMAL ACEH DENGAN MEMPERTIMBANGKAN EFEK DARI VARIASI KALENDER - Rasyada Assakhiy; Samsul Anwar; Fitriana AR (Jurnal Ekonomi dan Pembangunan, 2025)
Baitul Mal Aceh is an Aceh provincial government institution that is responsible for managing and distributing zakat, infaq and shadaqah (ZIS). Forecasting the potential of zakat in the future is needed by the Baitul Mal Aceh as one of the foundations for the preparation of ZIS management policies. This study aims to predict the potential of zakat collected in 2018 and 2019 by considering effects of calendar variations. The data used in this study is data realization of monthly zakat receipts starting from January 2015 to December 2017 obtained from Baitul Mal Aceh. The data was analyzed using the Autoregressive Integrated Moving Average with Exogenous Variable (ARIMAX) and Seasonal Autoregressive Integrated Moving Average (SARIMA) as comparative model. The results showed that the ARIMAX model with order ARIMA (2.0,2) (1,0,2) 12 , t, V 1 , ..., V 11 is much better than the SARIMA model with order ARIMA (0,1,2) ( 0,1,1) 12 based on indicators of the prediction accuracy (RMSE and MAPE). Realization of zakat receipts in 2018 and 2019 are estimated in the amount of Rp. 1,347,526,504 and Rp. 1,359,728,268. The forecasting results can be used as one of the references for the Baitul Mal Aceh in preparing the policy of distributing zakat in the coming years.